Shadow in the greenhouse. - Girvan, Helen (Philadelphia : Westminster Press, 1970)
Jocelyn Gates spends the summer in her uncle's nursery in an effort to find a stamp counterfeiter who also has an interest in exotic orchids.
Keywords: Mystery and detective stories